2019
DOI: 10.1049/iet-map.2018.5779
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimisation of super‐wideband monopole antenna with tri‐band notch using a transmission line model

Abstract: A study of monopole antenna for super‐wideband applications is presented. A compact patch antenna is suggested to enhance the overall covered bandwidth (BW), where a major improvement of the BW obtained in the range 2.6–23 GHz (BW of 20.4 GHz). Also, by creating slots in the patch and in the feed line; three band‐notches are created to reject different narrowband applications. The different antenna parameters are studied using a high‐frequency structure simulator (HFSS). The measured data of the fabricated ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is observed that for 3.5 GHz, the current was concentrated around the T‐shaped resonator, whereas, for 5.25 and 7.7 GHz, the current majorly lies around the corresponding U‐shaped slots (resonators). This specifies that at these frequencies, there is almost negligible radiations from the antenna 31 …”
Section: Results Fabrication and Measurementmentioning
confidence: 99%
“…It is observed that for 3.5 GHz, the current was concentrated around the T‐shaped resonator, whereas, for 5.25 and 7.7 GHz, the current majorly lies around the corresponding U‐shaped slots (resonators). This specifies that at these frequencies, there is almost negligible radiations from the antenna 31 …”
Section: Results Fabrication and Measurementmentioning
confidence: 99%
“…Although the proposed antenna is compact and operated under low frequency region 0.9 to 100 GHz, nonetheless the suppressed band is only one which falls outside the UWB band. Similarly, a SWB monopole antenna with tri-band notch characteristic is reported in [20], but all the rejection bands belong to UWB range. Moreover, the antenna do not support the lower frequency region.…”
Section: Introductionmentioning
confidence: 99%
“…Very few of SWB antennas offered single [14]- [17] dual [18]- [19], and triple [20] band notch characteristics. However, none of the design focused on band rejection outside the UWB range.…”
Section: Introductionmentioning
confidence: 99%
“…An optimization is used in Applied Wave Research (AWR) simulator to find the transmission line parameters such as resistance (R), inductance (L), and capaci-Fig. 1 Geometrical configuration of 9-point star-shaped (a) one-equilateral triangles, (b) twoequilateral triangles, (c) three-equilateral triangles, (d) four-equilateral triangles, (e) merge all triangles and (f) nine-point star tance (C) of the TLM equivalent circuit using the S 11 simulated parameters [16][17][18] of the proposed antenna. The 12-point star has been designed using four circles having three corners to make equilateral triangles with each radius 11 mm, and thus 9-point star will be obtained as shown in Fig 1 . The geometry of a compact CPW-fed SSMA is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%